Plan de negocios para la creación de una empresa para la comercialización de suplementos nutricionales naturales para deportistas - Ortiz Cobo, Jorge Enrique (2018)
The project aims to determine the social and economic viability of undertaking a basket of nutritional supplements for athletes and complementary personalized counseling services in Quito, Ecuador. The research began with the use of tools for the analysis of environments such as PEST analysis, PORTER forces and EFE matrix, providing a context for the nutritional supply industry (C1079.29). On the other hand, qualitative methods such as expert interviews and focus groups were used for market analysis, as well as quantitative analyses (surveys) to understand the needs and behavior of the target market. After the previous analysis, the business model presents a market opportunity based on the lack of a personalized basket for each sportsman and complementary services of nutritional and sports education. Given the lack of these benefits in the market, the company NUTRI-SPORT arises. The business offers 4 monthly home delivered baskets and the benefits of joining a sports and nutritional development bread with a professional nutritionist, truthful information on general and personal advice on nutrition and sports, as well as quarterly invitations to talks on a specific topic on the activities outlined above, all this in order for the athlete to achieve their goals more efficiently. Being a totally different product and services in the local market, a general strategy for the development of new products is proposed. As for the organizational structure, an organizational chart and its functioning were established to provide the best quality. Finally, a financial analysis was carried out, which showed that the business was entirely viable through indicators. In conclusion, the nutrition market focused on athletes has grown slightly in recent years, however, there is a hidden business opportunity given the lack of a personalized product and support services that offer an integrated development to the athlete.